Durable Complete Response to Pembrolizumab in Esophageal Squamous Cell Carcinoma With Divergent Microsatellite Status: A Case Report - Zeng, Tian; Zhang, Lei; Chen, Can; Zhao, Xiang; Liu, Xiaoqing; Ran, Fengwei; Yong, Tingting; Yang, Ying; Zhang, Henghui; Zhang, Yanling (Frontiers in Oncology, 2021)
Microsatellite instability-high (MSI-H) is widely believed to be a biomarker for immune checkpoint inhibitors (ICIs) such as pembrolizumab in solid tumors. However, due to the low prevalence of MSI-H in most cancers, it tends to be insufficient to identify whether patients should receive ICIs according to this biomarker alone. Here, we report a Chinese esophageal squamous cell carcinoma (ESCC) patient with unusual divergent MSI status between the primary lesion (MSS) and metastatic lesion (MSI-H) which developed after platinum-based therapy and radiotherapy. Both his primary and metastatic tumors responded well to pembrolizumab-containing therapies or pembrolizumab monotherapy and maintained a complete response for over 24 months. Whole-exome sequencing and multiplex immunohistochemistry were used to examine his tissue specimens. Notably, there were multiple high-frequency mutations of DDR (DNA damage repair) genes shared in the primary lesion and metastatic lesion, especially in the latter. Besides, we observed considerable degrees of infiltrating CD3+/CD8+ lymphocytes in both of his primary tumor and metastatic tumor without obvious difference, suggesting that the conversion of microsatellite status had little effect on the infiltration of lymphocytes. Collectively, given the predictive role of DDR alterations for ICIs in other malignancies, the alterations of DDR genes might also be promising biomarkers in ESCC individuals receiving ICIs.